2012
DOI: 10.1371/journal.pone.0033482
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Extension of the Yeast Mitochondrial DNA Polymerase Determines the Balance between Synthesis and Degradation

Abstract: Saccharomyces cerevisiae mitochondrial DNA polymerase (Mip1) contains a C-terminal extension (CTE) of 279 amino acid residues. The CTE is required for mitochondrial DNA maintenance in yeast but is absent in higher eukaryotes. Here we use recombinant Mip1 C-terminal deletion mutants to investigate functional importance of the CTE. We show that partial removal of the CTE in Mip1Δ216 results in strong preference for exonucleolytic degradation rather than DNA polymerization. This disbalance in exonuclease and poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…Structural modeling and site-directed mutagenesis studies indicate that family A DNA polymerases are deficient in 3′-5′ exonucleolysis of RNA primers because of a steric clash of the 2′-OH and conserved amino acids in the exonuclease domain (Lin et al, 2001). As previously reported (Viikov et al, 2011(Viikov et al, , 2012, the 3′-5′ exonuclease activity of Mip1 is distributive as a series of short intermediates from 23 to 2 nts are present during the time-course of the reaction. Accordingly to the differential in catalytic activity of Mip1 using an RNA or a DNA substrate, in the absence of dNTPs Mip1 degrades the DNA primers to a final product of 2 nts, whereas the RNA primer is degraded to 14 nts ( Fig.…”
Section: Heterologous Purification Of Mip1 Rpo41 Mtf1 and Rim1mentioning
confidence: 52%
See 2 more Smart Citations
“…Structural modeling and site-directed mutagenesis studies indicate that family A DNA polymerases are deficient in 3′-5′ exonucleolysis of RNA primers because of a steric clash of the 2′-OH and conserved amino acids in the exonuclease domain (Lin et al, 2001). As previously reported (Viikov et al, 2011(Viikov et al, , 2012, the 3′-5′ exonuclease activity of Mip1 is distributive as a series of short intermediates from 23 to 2 nts are present during the time-course of the reaction. Accordingly to the differential in catalytic activity of Mip1 using an RNA or a DNA substrate, in the absence of dNTPs Mip1 degrades the DNA primers to a final product of 2 nts, whereas the RNA primer is degraded to 14 nts ( Fig.…”
Section: Heterologous Purification Of Mip1 Rpo41 Mtf1 and Rim1mentioning
confidence: 52%
“…The transcription-dependent mtDNA replication mechanism requires that the 3′-5′ exonuclease activity of Mip1 does not degrade the transcribed RNA primer to a length at which it cannot be extended. DNA synthesis by Mip1 displays a balance between its 3′-5′ exonuclease and 5′-3′ polymerase activities In the presence of high concentrations of dNTPs, Mip1 performs coupled DNA polymerization and 3′-5′ exonucleolysis (Viikov et al, 2012). In the presence of dNTPs, one fraction of the DNA primer is degraded to 14 nts and other fraction of the primer is extended to 45 nts; however, the RNA primer is degraded with lower efficiency ( Fig.…”
Section: Heterologous Purification Of Mip1 Rpo41 Mtf1 and Rim1mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, arginine 1001, a very conserved residue in fungal polymerases, is important for the polymerase activity, since replacing it with isoleucine causes a petite frequency of 20% and a 50-fold higher point mutability compared to the wild type (Hu et al, 1995 ). In vitro analysis showed that the region 1038–1079, despite containing several positively charged residues, is important for efficient polymerization but not for processivity, which is increased in the absence of this region (Viikov et al, 2012 ). However, the exonuclease activity of the mutant Mip1 lacking the last 216 amino acids is similar to that of wild type Mip1, so that in the presence of low concentrations of dNTPs the balance between the exonuclease activity and the polymerase activity is tipped in favor of the first.…”
Section: Mip1 Biochemical Propertiesmentioning
confidence: 99%
“…However, the exonuclease activity of the mutant Mip1 lacking the last 216 amino acids is similar to that of wild type Mip1, so that in the presence of low concentrations of dNTPs the balance between the exonuclease activity and the polymerase activity is tipped in favor of the first. Similarly, the strand displacement activity is halved (Viikov et al, 2012 ).…”
Section: Mip1 Biochemical Propertiesmentioning
confidence: 99%